Aproximación periodística al estilo del entrevistado. El caso de Ramón María del Valle Inclán - Galindo Arranz, Fermín (Estudios sobre el Mensaje Periodístico, 2008)
The journalistic theory relating to the interview as a genre moves among the bordering space of the informative practice and the literary canon. This dichotomy allows to explore a journalistic genre in which the dominant guideline can be also imposed by the interviewee´s style. The analysis of a vast sample consisting in a hundred of interviews done Don Ramón María del Valle-Inclán during the first third of the twentieth century clearly ilustrates this circunstance.
Keywords: Journalism; Interview; Valle-Inclán